2010
DOI: 10.1089/neu.2009.1049
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Parametric Mapping and Cluster Counting Analysis of [18F] FDG-PET Imaging in Traumatic Brain Injury

Abstract: In this study we investigated regional cerebral glucose metabolism abnormalities of [(18)F] fluorodeoxyglucose (FDG) positron emission tomography (PET) imaging in traumatic brain injury (TBI). PET images of 81 TBI patients and 68 normal controls were acquired and a word list learning task was administered during the uptake period. The TBI group included 35 patients with positive structural imaging (CT or MRI) findings soon after injury, 40 patients with negative findings, and 6 cases without structural imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Previous work suggested that complementary analyses should be used in studies comprising of traumatic patients. Some of these patients may exhibit extreme focal lesions and, as a result, any statistical inference could be driven by such outliers [28]. Previous studies have located various subprocesses of verbal working memory in structures of the left inferior frontal gyrus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggested that complementary analyses should be used in studies comprising of traumatic patients. Some of these patients may exhibit extreme focal lesions and, as a result, any statistical inference could be driven by such outliers [28]. Previous studies have located various subprocesses of verbal working memory in structures of the left inferior frontal gyrus [29].…”
Section: Discussionmentioning
confidence: 99%
“…When normal controls are compared with patients with a variety of TBI injuries, PET scans show that, in aggregate, patients with documented TBI had lower glucose uptake across wide swaths of cortex, including the frontal and parietal regions. These areas of reduced metabolism appear even when other CT or MR scans show no particular structural damage [65]. What the study also revealed, though, is that normal controls often have significant areas of hypometabolism too.…”
Section: Challenges In Using Tbi Brain Data In Legal Settingsmentioning
confidence: 49%
“…We administered 5 mCi of fluorodeoxyglose-F18 (FDG), and during FDG uptake, the patients performed the serial verbal learning test (Hazlett et al, 2010), which has been used in traumatic brain injury studies (Zhang et al, 2009). After approximately 32 min, the patient was positioned in a Siemens/CTI ECAT HR+ scanner (Siemens, Medical Systems, Inc., 810…”
Section: Brain Imagingmentioning
confidence: 99%
“…Furthermore, while conventional T1-and T2-weighted imaging techniques are relatively insensitive to the detection of mild neurotrauma, position emission tomography (PET) has been used to identify suboptimal brain function in the absence of structural lesions (Ruff et al, 1989;Ruff et al, 1994;Chen et al, 2003;Belanger et al, 2007;Kato et al, 2007;Zhang et al, 2009;Kim et al, 2010;Provenzano et al, 2010;Peskind et al, 2011;Byrnes et al, 2014;Buchsbaum et al, 2015). Thus, we examined patterns of fluorodeoxyglucose-F18 (FDG) uptake in PET studies carried out in veterans with spontaneous failure on the TOMM who participated in a research protocol, were assured of the confidentiality of their test scores, and therefore had no benefit eligibility or financial incentive for poor performance.…”
Section: Introductionmentioning
confidence: 99%